The Front Office Strategy on Service Quality Improvement - Made Windy Septariani; I Gusti Putu Sutarma; Made Sudiarta; Ni Made Sudarmini (International Journal of Glocal Tourism, 2020)
Purpose: This research aims to determine the strengths, weaknesses, opportunities, and threats in improving the quality of service to guests staying at 5 star hotel in Seminyak, Kuta, Badung, Bali. Research methods: The method of data analysis is a descriptive qualitative, descriptive quantitative, the matrix of IFAS, EFAS, IE Matrix, and SWOT analysis (strength, weakness, opportunity, and threat). This research sample uses 27 people coming from the management and team of Front Office Department. Findings: The results of this analysis show that there are internal and external factors affecting the improvement of the quality of front office services that get from the results of the questionnaire and interviews. Implication: The advice that can be given is to maintain cleanliness in the villa area to avoid complaints and add staff to the front office to help accelerate operational activities.